Whey permeate integral valorisation via in situ conversion of lactose into lactulose in an electro-activation reactor modulated by anion and cation exchange membranes. (February 2019) - Djouab, Amrane; Aïder, Mohammed
Abstract: Whey permeate (WP) was valorised through in situ isomerisation of lactose into lactulose by electro-activation. The effect of electric current intensity and salt (CaCl2, KCl and MgCl2 ) on the amount of lactose conversion into lactulose using WP (6%, w/w) and pure lactose (5%, w/w) solutions was studied. Lactose was converted into lactulose at a level of 35.1% when KCl at current intensity of 330 mA for 21 min of electro-activation was applied to WP; and 38.66% when KCl at current intensity of 330 mA for 14 min was applied to lactose solution. The use of WP in both the central and cathodic compartments without addition of salt yielded 39.78% lactulose after 35 min of electro-activation at 330 mA. Application of electro-activation to WP and lactose solutions enhanced product antioxidant capacity. Scanning electron microscopy and calculation of the global electrical resistance of the reactor did not reveal any membrane fouling.